2013
DOI: 10.1002/adma.201302447
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electroluminescence in Planar Graphene/SiO2 Memristors

Abstract: Electroluminescence and resistive switching are first realized simultaneously in graphene/SiO2 memristor devices. The electroluminescence peaks can be tuned between 550 nm and 770 nm reliably via setting the device to different resistance states by applying different voltages. The combination of resistive switching and electroluminescence may bring new functionalities for these memristor devices which are fully compatible with silicon-based electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 35 publications
11
49
0
1
Order By: Relevance
“…The RESET transition is modeled as being the result of Fowler-Nordheim electron tunneling into the H 3 O + defect (possibly current-induced Joule heating due to large current flow through the filament) that stimulates proton release and electrochemical reactions to reform (SiH) 2 and (SiOH) 2 (Figure 2f) [60]. The band diagrams shown in Figure 4b are found to be consistent with measured electron energy barriers [60] and electroluminescence results reported for similar devices [62]. -based 1D-1R architecture can mimic spike-timingdependent plasticity (STDP), a biological process that adjusts the strength of connections between two neurons in a synapse gap junction region that is an electrically conductive link between the pre-and postsynaptic neurons.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The RESET transition is modeled as being the result of Fowler-Nordheim electron tunneling into the H 3 O + defect (possibly current-induced Joule heating due to large current flow through the filament) that stimulates proton release and electrochemical reactions to reform (SiH) 2 and (SiOH) 2 (Figure 2f) [60]. The band diagrams shown in Figure 4b are found to be consistent with measured electron energy barriers [60] and electroluminescence results reported for similar devices [62]. -based 1D-1R architecture can mimic spike-timingdependent plasticity (STDP), a biological process that adjusts the strength of connections between two neurons in a synapse gap junction region that is an electrically conductive link between the pre-and postsynaptic neurons.…”
Section: Resultssupporting
confidence: 80%
“…In recent studies, a possible proton exchange model consistent with the observed resistive switching I-V response has been proposed, as shown in Figure 2f [59,60]. Several studies have used transmission electron microscopy (TEM) to document the presence of Si nanocrystals within the CF [43,61,62], but it is not yet clear whether resistive switching (RS) is the result of an overall increase in nanocrystal size or whether switching occurs in "GAP" regions in between nanocrystals. Most models of ReRAM switching involve the drift or diffusion of O 2− ions (or oxygen vacancy defects) [39], but these models cannot explain the unconventional I-V response.…”
Section: Resultsmentioning
confidence: 94%
“…The Si nanocrystals observed using transmission electron microscopy (TEM) of SiO x devices have been associated with reversible switching where they are thought to increase in size in the LRS, thus bringing neighboring crystals closer together and increasing conductivity, 32 and where a transformation between amorphous and crystalline phases can occur within the nanocrystals. 33 We view reversible switching as being related to defect transformations near the nanocrystal surfaces and in the regions between nanocrystals, similar to models described by Mehonic et al for switching in Si-rich oxides.…”
Section: B Temperature Dependence Of Current Transport Behaviors Andmentioning
confidence: 99%
“…Zhang's group explored various 2D material-based nanodevices for electronic applications, such as graphene nanoelectromechanical system (NEMS) switch devices, ultrasensitive graphene strain sensors and electronic skin, graphene-based charge-trapping memories, and graphene nanogap multilevel memristor devices (38)(39)(40)(41)(42)(43)(44)(45)(46). They also demonstrated highly sensitive humidity sensors based on monolayer MoS 2 films with clean surfaces.…”
Section: Device Applications Based On 2d Materialsmentioning
confidence: 99%